2017
DOI: 10.1038/s41598-017-11983-7
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent electrical transport properties in Co nanocluster-assembled granular films

Abstract: A series of Co nanocluster-assembled films with cluster sizes ranging from 4.5 nm to 14.7 nm were prepared by the plasma-gas-condensation method. The size-dependent electrical transport properties were systematically investigated. Both of the longitudinal resistivity () and saturated anomalous Hall resistivity () continuously increased with the decrease of the cluster sizes (d). The firstly increased and then decreased with increasing the temperature for all samples, which could be well described by involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
(50 reference statements)
1
0
0
Order By: Relevance
“…The mean diameters of the clusters were determined using ImageJ as described by Rasband . The larger cluster size associated with the best-performing film coincided with an improvement in conductivity, and this phenomenon has also been seen by Zhang et al who found that increased cluster diameters decreased film resistivity. Thus, the low electronic resistivity of the best-performing film (i.e., 7 Ω·m), coupled with an improvement in the Si cluster volume-to-surface area ratio has resulted in improved capacity retention and ICE compared to the worst-performing film (i.e., 97 kΩ·m).…”
Section: Resultssupporting
confidence: 70%
“…The mean diameters of the clusters were determined using ImageJ as described by Rasband . The larger cluster size associated with the best-performing film coincided with an improvement in conductivity, and this phenomenon has also been seen by Zhang et al who found that increased cluster diameters decreased film resistivity. Thus, the low electronic resistivity of the best-performing film (i.e., 7 Ω·m), coupled with an improvement in the Si cluster volume-to-surface area ratio has resulted in improved capacity retention and ICE compared to the worst-performing film (i.e., 97 kΩ·m).…”
Section: Resultssupporting
confidence: 70%